MOTIVASI MAHASISWA MENGIKUTI PERKULIAHAN DENGAN SISTEM E-LEARNING - annisa agata (Universitas Mitra Indonesia, 2023)
The Covid-19 pandemic that has occurred since 2019 has caused changes, especially in the education sector. Educational activities that were initially carried out face-to-face turned into an online system as an effort to prevent the spread of the COVID-19 virus. The purpose of this study is to determine the motivation of students in attending lectures during the COVID-19 pandemic. The type of research is quantitative with a descriptive research design. The population in this study was students of the Nursing Study Program at Mitra Indonesia University as many as ± 387 students with sampling techniques using snowball sampling, with a total sample of 94 responders. The results of the study found that the type of lecture media most often used was zoom meetings, which were 61 respondents (64.9%), the motivation of students in attending lectures was mostly not good, namely as many as 50 respondents (53.1%). This research can be a foundation for educators to increase student motivation during the COVID-19 pandemic by utilizing various digital platforms or modifying the learning process with blended learning methods.